The efficacy of combined bright light and melatonin therapies on sleep and circadian outcomes: A systematic review. (August 2021) - Cheng, Daniel Chih Yung; Ganner, James L.; Gordon, Christopher J.; Phillips, Craig L.; Grunstein, Ronald R.; Comas, Maria
Summary: The aim of this systematic review was to investigate the effects of combined melatonin and bright light therapies on improved sleep and circadian outcomes. We conducted a systematic review that resulted in a total of eight papers meeting criteria. Four papers investigated the effectiveness of combined therapy in inducing a circadian phase shift on healthy participants. Combined therapy outperformed single light and melatonin therapies in phase advancing, but not in delaying, dim light melatonin onset (DLMO). The other four papers investigated the effect of combined therapy on sleep outcomes. Two of them were performed in elderly populations suffering from cognitive decline and two in delayed sleep-wake phase disorder (DSWPD) patients. While combined therapy was more beneficial than single therapy in elderly populations it did not show any benefit in DSWPD patients. The reported adverse effects of melatonin in elderly populations must be carefully considered. Future studies should investigate the separate and combined effect of melatonin and bright light on sleep and circadian outcomes in different target populations.